Processo de trabalho em saúde: uma análise das condições de trabalho dos assistentes sociais no âmbito hospitalar - Meneses, érika Silva (2010)
This paper presents the survey results: PROCEDURE FOR WORK IN HEALTH: an analysis of working conditions of social workers in hospitals. Analyzes the inclusion of social workers in work processes in healthcare, specifically in the public hospital, from the objective conditions of work, according to which materializes professional action. The aim is to understand them from the point of view of its relationship with users and other health professionals through the privatization of health, which prevents the Unified Health System (SUS), limiting the operation of the services and the guarantee of rights. The approach to the reality studied was through theoretical and methodological procedures based on the qualitative and quantitative research, focusing on documentary research, observation, semi-structured interview and the theoretical foundation. It is observed that the inclusion of social workers in this context arises from the demands derived from expressions of social issues, "raw material" of professional work, and the gaps resulting from contradictions in the process of rationalization / reorganization of the SUS, meaning that the needs the population are confronted with the content and form of organization of services. At the hospital, the professional actions are developed through the shift, space contradictory clash between the collective and individual, in which individual activities are prioritized and ad hoc unplanned and reduced to the solution of "problems" of users, through actions assistance in an emergency and bureaucratic. These findings emphasize the inadequacy of space and lack of minimum conditions of service to users, which undertakes the professional with regard to ethical and political principles of the profession, since it is the responsibility and duty of the social guarantee the secrecy and privacy of users what is revealed during the process of professional intervention. The professional social workers is permeated by the diversity of skills and competence; lack of planning activities, by incorporating the institutional discourse at the expense of professional goals, by knowing the Code of Professional Ethics, for small number of professionals, the increasing number informality; by poor working conditions and wages; by discouraging research and participation in social policy councils, as well as professional training